Chapter Understanding the sensory characteristics of edible insects to promote entomophagy: A projective sensory experience among consumers - Piscitelli, Alfonso (Proceedings e report, 2021)
In recent years, a remarkable number of studies have investigated sensory characteristics, such as flavor and texture, of edible insect and insect-based foods, their contribution to consumers' attitudes toward edible insects are important in consumer appeal and their willingness to try eating insects in the future. This paper addresses the problem of describing the sensory characteristics aof edible insect and insect-based foods in terms of preferences. To this end, we conducted a study to explore the representations of sensory experiences related to an insect-based dish involving a voluntary sample of 154 consumers. The quasi-experiment, which we have called projective sensory experience (PSE), follows a two-step procedure. In the first step, we asked the participants to imagine tasting an insect-based dish and then to rate, from 1 (imperceptible) up to 10 (very perceptible), the following taste-olfactory sensations: Sapidity, Bitter tendency, Acidity, Sweet, Spiciness, Aroma, Greasiness-Unctuosity, Succulence, Sweet, Fatness, Persistence. In the second step, we asked our interviewees to indicate, through a specific check-list, which was the most disturbing and least disturbing taste-olfactory sensation imagined. We collected data from May to July 2020 by using an anonymous on-line questionnaire. Results could help understand the sensory characteristics of "insects as food" that should be used or avoided, for example, in communication aimed at promoting familiarity with edible insects and improving the acceptability of insects as a novel food.